Affective Communication in Hyperreality: Reconstructing Public Communicator Competence - Razali, Geofakta; Wahyu Kristian Natalia (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
This study aims to analyse the urgency of integrating psychological and affective dimensions into the competence of public communicators in the era of hyperreality, in which the boundaries between reality and its representations are increasingly blurred, thereby influencing how messages are produced, perceived, and interpreted. In a social context characterised by simulation and heightened emotional intensity, communicators' ability to manage affect is essential to ensure that messages are not only informative but also emotionally resonant. Employing a mixed-methods design with a sequential explanatory strategy, the quantitative phase involved 120 active public communicators—comprising influencers, journalists, public speakers, and PR/marketing practitioners—who were selected through purposive sampling. The Affective Communication Test (ACT) was used to assess affective communication capability, and the data were analysed descriptively to identify affective profiles and determine participants for the qualitative phase. The qualitative stage employed a phenomenological approach and was conducted through semi-structured interviews with 15 participants representing the highest and lowest ACT scores. These interviews explored their personal experiences interpreting, managing, and responding to affective dynamics in both digital and physical environments. The findings indicate that communicators with high ACT scores demonstrate more developed emotional awareness, more adaptive, audience-oriented strategies, and the capacity to cultivate meaningful resonance in hyperreal contexts. In contrast, communicators with lower scores tend to prioritise technical aspects of messaging while overlooking affective dynamics, thereby rendering their messages more vulnerable to loss of depth and meaning. This study recommends enhancing affective literacy and psychology-based training to develop public communication competencies. Theoretically, the findings contribute to the formulation of a grounded theory–based conceptual framework for understanding communicator competence in postmodern society.